2012
DOI: 10.1016/j.otsr.2011.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Severe corrosion after malpositioning of a metallic head over the Morse taper of a cementless hip arthroplasty. A case report

Abstract: Morse tapers are frequently used in total hip replacement to achieve precise adjustment of lengths and femoral offset. Mechanically, they do not raise any specific problems so long as strict positioning requirements are observed and elements from different manufacturers are not mixed together. We report a case in which the implant induced unexplained pain at 2 years, in relation to a defective fit between the metallic head and the Morse taper. Asymmetric partial fit of the head onto the taper was detected on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…14 Among the many factors that can affect implant performance, the corrosive nature of the physiological environment plays a significant role. Metal-on-metal (MoM) hip replacements, typically made of CoCrMo alloys, degrade because of the synergistic effects of mechanical wear from metal–metal contact and electrochemical reactions with salts, proteins, and other organic species.…”
Section: Introductionmentioning
confidence: 99%
“…14 Among the many factors that can affect implant performance, the corrosive nature of the physiological environment plays a significant role. Metal-on-metal (MoM) hip replacements, typically made of CoCrMo alloys, degrade because of the synergistic effects of mechanical wear from metal–metal contact and electrochemical reactions with salts, proteins, and other organic species.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of factors have been identified as possible contributors to the observed material loss including micromotion due to angle mismatch, insufficient assembly forces, galvanic cell creation due to differential head and stem materials and increased frictional torque [12][13][14][15][16]. Determination of the volume of material loss at this interface is vital in determining the relative contribution that this makes to the overall failure of metal-on-metal hip bearings [18][19][20][21][22][23][24][25]. Most previous studies relied on either the visual assessment of taper damage (which can be clearly seen in figure 2) or measurement by means of coordinate measuring machines [5,10].…”
Section: Figurementioning
confidence: 99%
“…Two of the final articles were removed because they addressed corrosion secondary to stem loosening and a knee modular revision component. This left nine articles focused on corrosion in femoral hip components [9,10,23,29,32,37,42,46,47].…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…There were nine studies identified addressing the surgical treatment of implant failures secondary to taper corrosion (Table 5) [9,10,23,29,32,37,42,46,47]. Eight articles were case report studies and one was Level IV.…”
Section: Treatment Of Corrosionmentioning
confidence: 99%